IMOBILISASI BIOMASSA DAN CRUDE ENZYME JAMUR UNTUK DEKOLORISASI PEWARNA LIMBAH INDUSTRI TEKSTIL - , MUHAMMAD SAID HASNAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Textile waste water contain toxic compound that can cause environmental pollution. The RedX 8B and Direct Turquois are two kinds of sintetic dye in textile industry. RedX 8B is azo compound and Direct Turquois is Phthalocyanine compound which are can be degraded by lignolitic producing fungi. The purpose of this research is to remediase those textile dye using immobilization technique to increase remediationâs quality. This research using six fungal isolates, those were K1, K2, K3, JYGC 1, TPA 4, and KRMS 5. Crude enzyme and biomass of the selected fungi were immobilized using calcium alginate with three kinds of diametric beads that were 0.16, 0.25, 0.36 cm for crude enzyme, also 0.24 and 0.35 cm for biomass. The experiment of applicationâs beads to waste water also done with 5x and 10x dilution. The results showed that K1, K3, and KRMS 5 are the selected fungi which have high total decolorizationâs activities from RedX 8B and Direct Turquois are 2.4 (K1), 2.38 (K3), and 2.4 (KRMS 5). The highest of diameter size are 0.35 cm in the rate of decolorization. The highest decolorizationâs activity from RedX 8B in beads application with 5x dilution is 34.82% for crude enzyme and 55.08% for biomass. The highest decolorizationâs activity from Direct turquoise in beads application with 10x dilution is 59.89% for crude enzyme and 89.07% for biomass. Based on the macroscopic and microscopic characteristics, K1 and KRMS 5 were determined as Penicillium sp., and K3 as Aspergillus sp. Keyword: decolorization, textile waste water, immobilization, fungi, crude enzyme